Unique lexical units in English and Uzbek Advertising texts. - Kilicheva Mekhriniso Radjabovna; Utkirova Shakhnoza Abbos kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Advertising language is a specialized variant of linguistic communication designed to capture attention, convey persuasive messages, and influence consumer behaviour. Unlike ordinary text, advertising discourse blends creativity with economy of expression, often employing distinctive lexical units—words and phrases that are both impactful and memorable. In the global context, English advertising language has developed a rich inventory of such units characterized by appeals to emotion, instant recognition, and brevity. In contrast, Uzbek advertising texts—shaped by different cultural, communicative, and linguistic traditions—tend to integrate descriptive expressions grounded in local values. Comparative linguistic studies show that while both languages aim to persuade, the forms and lexical content reflect differing cultural priorities and persuasive strategies.